Intellectual History Meets Literary Studies, or What Happens to Ideas in Literature (ENTHYMEMA International journal of literary criticism, literary theory, and philosophy of literature, 2014)
Ideas in literature are immersed into a huge mass of non-conceptual discourses; take very often a metaphoric form; they are in many texts entrusted to fictional persons, to imaginary characters; they have a specific, and even paradoxical, form of responsibility. These features of ideas in literature, making them a privileged object of study in intellectual history, are exemplified by Théophile Gautier’s novel Mademoiselle de Maupin, more precisely by its preface, considered to be a manifesto of Art for Art’s Sake doctrine.